BRAF in non-small cell lung cancer (NSCLC): Pickaxing another brick in the wall. (May 2018) - Leonetti, Alessandro; Facchinetti, Francesco; Rossi, Giulio; Minari, Roberta; Conti, Antonia; Friboulet, Luc; Tiseo, Marcello; Planchard, David
Highlights: BRAF mutations, accounting for about 2% of NSCLC, can be divided in V600E and non-V600E. Dabrafenib and trametinib are FDA and EMA approved for the treatment of BRAF V600E mutant NSCLC. BRAF and/or MEK inhibitor activity should be further investigated in non-V600E variants. BRAF mutations represent an emerging mechanism of resistance to third generation EGFR-TKIs. A better characterization of acquired mechanisms of resistance to BRAF and/or MEK inhibitors is needed. Abstract: Molecular characterization of non-small cell lung cancer (NSCLC) marked an historical turning point for the treatment of lung tumors harboring kinase alterations suitable for specific targeted drugs inhibition, translating into major clinical improvements. Besides EGFR, ALK and ROS1, BRAF represents a novel therapeutic target for the treatment of advanced NSCLC. BRAF mutations, found in 1.5–3.5% of NSCLC, are responsible of the constitutive activation of mitogen activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) pathway. Clinical trials evaluating the efficacy of the BRAF inhibitor dabrafenib in combination with the downstream MEK inhibitor trametinib in metastatic BRAF V600E -mutated NSCLC guaranteed FDA and EMA rapid approval of the combination regimen in this clinical setting. In line with the striking results observed in metastatic melanoma harboring the same molecular alteration, BRAF and MEK inhibition should be considered a new standard of care in this molecular subtype of NSCLC. In the present review, we propose an overview of the available evidence about BRAF in NSCLC mutations (V600E and non-V600E), from biological significance to emerging clinical implications of BRAF mutations detection. Focusing on the current strategies to act against the mutated kinase, we moreover approach additional strategies to overcome treatment resistance.